2020
DOI: 10.1186/s40885-019-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure trajectory modeling in childhood: birth-cohort study

Abstract: Background: Systolic blood pressure (SBP) and diastolic blood pressure (DBP) tends to increase with age and increase in proportion to body weight and height. Recent epidemiological and longitudinal cohort studies have found that high BP in children can be progressed into hypertension (HTN) in adulthood. Therefore, the aim of this study is that we monitor and analyze the tendency of the BP trajectory in children from the age of 3 years to the age of 10 years. Method: A total of 767 subjects were gathered from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…Regarding the persistence of cMetS, several studies evaluated the correlation coefficient 30 , 31 , but no study has tried to identify trajectory patterns of cMetS using long-term follow-up data. In a previous study using the same data source, the trajectory of BP, a component of MetS, was analyzed using data from 65 subjects repeatedly measured from 3 to 10 years of age, and the results were similar to the results of this study 32 . The identified trajectory patterns showed that cMetS values were clearly distinguished by trajectory groups from the early period of life and remained stable during a long follow-up period from 3 to 12 years of age.…”
Section: Discussionsupporting
confidence: 69%
“…Regarding the persistence of cMetS, several studies evaluated the correlation coefficient 30 , 31 , but no study has tried to identify trajectory patterns of cMetS using long-term follow-up data. In a previous study using the same data source, the trajectory of BP, a component of MetS, was analyzed using data from 65 subjects repeatedly measured from 3 to 10 years of age, and the results were similar to the results of this study 32 . The identified trajectory patterns showed that cMetS values were clearly distinguished by trajectory groups from the early period of life and remained stable during a long follow-up period from 3 to 12 years of age.…”
Section: Discussionsupporting
confidence: 69%
“…LVH and LAE are an important cardiac component of HMOD, and HMOD is associated with an increased risk of cardiovascular disease in patients with hypertension [ 19 ]. Because LVH comes from a maladaptive response to chronic overload of LV afterload, the antihypertensive medications which reduce LV afterload can reverse LVH [ 20 ]. Thus, identifying high-risk subjects developing HMOD can give us a chance to prevent future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…However, current risk prediction models include BP levels only at one time of the risk prediction and neglect the effect of BP levels over time [ 7 ]. The BP trajectory model can describe the course of BP variables over time [ 20 ]. Also, SBP increases with aging, and the patterns of BP change with aging may differ among individuals [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, NCDs and primarily cardiovascular diseases have taken over as the chief cause of morbidity and mortality, accounting for 71% of annual deaths globally [ 1 ]. Accumulating evidence is shedding light on the tracks of NCDs and specifically cardiovascular diseases in the preadulthood, highlighting the significance of early environmental exposures [ 2 8 ]. Accordingly, childhood and adolescence could be considered opportunities to prevent NCDs from happening later in life through environmental and behavioral interventions.…”
Section: Introductionmentioning
confidence: 99%